Radiological study to determine the association of proximal femoral geometry in hip fractures - Sivaprasad, K.; Patil, Rachna (International Journal of Research in Medical Sciences, 2023)
Background: In literature there is scarcity of documentation to test the relationship of radiological geometry of proximal femur with incidence and patterns of hip fractures especially in Indian population. In this study radiological parameters like femoral neck length (FNL), hip axis length (HAL), neck shaft angle (NSA), femoral neck diameter (are measured in standardized digital pelvis radiograph of patients with hip fractures presented at a tertiary care hospital and efforts were made to establish a relationship of these parameters with the pattern of hip fractures in Indian population. Methods: Total of 72 patients attending orthopaedics outpatient clinic or admitted into the hospital with proximal femoral fractures were included in the study. Thorough history and clinical examination data were obtained. Radiographs and necessary investigations were done and FNL, HAL, NSA was calculated. Analysis was done using SPSS package version 26. Results: Among the 72 patients included in the study, the mean age of the patients is 65 years with a SD of 13.64. The mean FNL was 2.452 cm with a SD of 0.471. The mean HAL was 11.1547cm and SD of 1.062. The mean NSA was 124.56degree with a SD of 3.339. The distribution of NSA is statistically insignificant at p<0.05. The mean NSA of extracapsular fracture and Intracapsular fracture in 51-60 years is 123.1956 and 125.7750 with SD of 2.58782 and 3.99555 is respectively. The p=0.151 and is statistically significant. Conclusions: In our study, we concluded that the HAL is significantly increased for intracapsular fractures than for Extracapsular fractures in old age group of 51-60 years. In our study, we could not establish any significant correlation between FNL, HAL and NSA in any age group for any fracture type.